PERSEPSI BERKEHIDUPAN BERMASYARAKAT MENURUT PUISI â€œMENDING WALLâ€ KARYA ROBERT FROST: SUATU TINJAUAN STILISTIKA - Jumino, Jumino (Faculty of Humanities, Diponegoro University, 2014)
Human beings are one the best living creatures God created in the world. While living, as their existence, they have duties to do as individual creature,Â as social creature, and as God creature. Each existence has its consequences. Through his poem â€œMending Wallâ€, Robert Frost views human existence as social creature that needs relations to the others surrounding. One of human relations happens is described by two opposing characters on human beings within the poem. To make the poem more interested and challenging, Frost applied stylistic writing by choosing good diction and image of words used packed in some figurative language. The figurative language involves personification, metaphor, and symbol. In this article, the writer analyzes the elements of stylistics used by Frost in the poem â€œMending Wallâ€.